Kualitas Pelayanan Administrasi Kependudukan Dan Pencatatan Sipil : Studi Kasus Pelayanan Publik Di Kelurahan Kedung Baruk - Joko Widodo; Tariza Noviranti Muhaling (Jurnal Relasi Publik, 2024)
"Public service" is the provision of services by the government, private entities on behalf of the government, or private entities to the public, either funded or free of charge, to meet the needs or interests of the community. The Kedung Baruk Village Office is one of the networks responsible for various public services, where service quality is a crucial point in the administration of public services. The Kedung Baruk Village Office faces challenges in maintaining and improving the quality of services they provide. Therefore, this research aims to conduct an in-depth review of the quality of public services at the Kedung Baruk Village Office, focusing on population administration and civil registration services. In this study, the author uses a descriptive qualitative research method, with data collection techniques including documentation, interviews, and observation. The primary and secondary data obtained by the author come from observation, documentation, and interviews.